Terahertz waveguide and VNA calibration - Sagayaraj, Illangkathir (Nanyang Technological University, 2023)
As the world’s need for wireless communications grows at unprecedented rates, it is very crucial to continue developing technology that is able to accommodate high speed transmission and reception. As such, it is only natural for the shift from 5G communications to 6G communications to occur.